INFORMATION TECHNOLOGY ON ECONOMIC GROWTH AND STABILITY - T Handayani; R T Aprilia; O Widaningsih; F N Kesuma; R Jumansyah (President University, 2021)
This research aims to analyze how the role of information technology on economic growth and stability. Information technology at this time can be an important indicator of economic growth and stability. It is hoped that with information technology, a country can increase the production of goods and services. This research used descriptive qualitative in nature and with a literature review. The sample in this study is the growth and stability that occurs in various countries, especially Indonesia. This research discusses how information technology helps in increasing growth and stability in a country. The results of this study indicate that information technology is very influential on economic growth and stability. The role of information technology has the most influence on economic growth is to increase the effectiveness of resource allocation in organizations by 85.2%. and 77.8% of the response to information technology can increase the amount of investment in a company. The use of information technology will also speed up the production process by reducing the time needed to sort components and raw materials while reducing the potential for errors. it can be concluded that information technology is very influential in the economic growth rate of 96.3% respondents